2016
DOI: 10.1185/03007995.2015.1135789
|View full text |Cite
|
Sign up to set email alerts
|

Basal insulin persistence, associated factors, and outcomes after treatment initiation among people with type 2 diabetes mellitus in the US

Abstract: Objective To assess basal insulin persistence, associated factors, and economic outcomes for insulin-na€ ıve people with type 2 diabetes mellitus (T2DM) in the US. Research design and methods People aged 18 years diagnosed with T2DM initiating basal insulin between April 2006 and March 2012 (index date), no prior insulin use, and continuous insurance coverage for 6 months before (baseline) and 24 months after index date (follow-up period) were selected using de-identified administrative claims data in the US. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
65
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(77 citation statements)
references
References 19 publications
7
65
5
Order By: Relevance
“…23 Increased pharmacy costs were offset by savings in other areas in three of the other persistence studies, although not enough to result in a reduction in total health care costs in more persistent patients 11,17,24. One US claims analysis reported lower all-cause medical costs (costs not disaggregated) in the first year after treatment initiation in patients who continued basal insulin compared with interrupters or discontinuers ( P ≤0.022; Figure 3A), but the higher pharmacy costs also incurred by this group resulted in no difference in total health care costs (medical plus pharmacy) between patient cohorts 17. Using Japanese claims data, it was also shown that higher pharmacy expenditures in patients with T2DM who continued basal insulin therapy were not completely offset by significant reductions in inpatient costs reported in this group compared with interrupters or discontinuers ( P ≤0.039; Figure 3B).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…23 Increased pharmacy costs were offset by savings in other areas in three of the other persistence studies, although not enough to result in a reduction in total health care costs in more persistent patients 11,17,24. One US claims analysis reported lower all-cause medical costs (costs not disaggregated) in the first year after treatment initiation in patients who continued basal insulin compared with interrupters or discontinuers ( P ≤0.022; Figure 3A), but the higher pharmacy costs also incurred by this group resulted in no difference in total health care costs (medical plus pharmacy) between patient cohorts 17. Using Japanese claims data, it was also shown that higher pharmacy expenditures in patients with T2DM who continued basal insulin therapy were not completely offset by significant reductions in inpatient costs reported in this group compared with interrupters or discontinuers ( P ≤0.039; Figure 3B).…”
Section: Resultsmentioning
confidence: 98%
“…Pharmacy/drug/medication costs were specifically reported as being included in the analyses of all studies, 13 reported including inpatient, hospitalization, and/or emergency room (ER) costs, and outpatient or ambulatory costs were reported in 10 studies. Some studies were, however, vague about what expenses were actually considered, instead just referring to “medical” or “total” costs in their methodologies 11,1317. Only two studies considered the costs of nonadherence outside the health care system: patient co-payments were included in one study and out-of-pocket expenses were included in another 18,19.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations